Spectrum of Chest Computed Tomography (CT) Findings of COVID-19 Pneumonia Patients in B & C Hospital, Birtamode, Jhapa, Nepal - Shrestha, Manmohan Bir; Sharma, Umesh Kumar; Thapaliya, Suraj; Pokhrel, Abishek; Shrestha, Shreya; Nepal, Prajwal; Rai, Ujwal (Medical Journal of Eastern Nepal, 2022)
Background: Coronavirus disease outbreak, first reported in Wuhan, China in December, 2019 is a WHO declared pandemic. Chest tomography (CT) findings can supplement in the diagnosis of COVID-19 pneumonia. Methods: This was a retrospective descriptive study in 40 patients with reverse transcriptase polymerase chain reaction (RT-PCR) positive patients with respiratory symptoms who underwent Computed tomography (CT) chest. This retrospective study was conducted at B & C Medical College Teaching Hospital, Birtamode, Jhapa, Nepal. Results: Total 40 patients, more than 3 lobes of lung involved in all 40 patients (100 %). Only ground-glass opacities seen in 11 patients, only consolidative opacities seen in 5 patients, both ground-glass and consolidation seen in 23 patients, and 1 patient had neither of them. Subpleural linear density was present in 16 patients (40%). Pleural effusion was present in 8 patients and crazy paving pattern in 9 patients. Total lung severity score range from 3 to 19 with a mean score of 9.8. Conclusions: Characteristic chest Computed tomography (CT) findings were observed in Corona virus disease 2019 infection, which are helpful to the radiologists, clinical physicians and other public health officials in the early detection and diagnosis of this global health emergency.